Livelihoods Sustainability of Tuna Handline Fishery in Buru Island - Laitupa, Jufri Pachri; S. Baskoro, Mulyono; Wiryawan, Budy; Mustaruddin, Mustaruddin (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This study aims to assess the status of the sustainability and the factors supporting or hindering the livelihoods of tuna hand line fishermen on Buru Island which includes Buru and south Buru regency. This study applied the FLIRES (Fisheries Livelihood Resilience) Check instrument which combines the principles of the Sustainable Livelihood Analysis (SLA) with the RAPFISH approach. Data collection started from March to August 2020, through observations and interviews of tuna hand line fishermen respondents in seventeen coastal villages in Buru and South Buru. Data were analyzed using RAPFISH which includes multidimensional scaling (MDS), leverage and monte carlo analysis. The results obtained, some index values of livelihood’s sustainability of tuna hand line fishers in the research location, in six fields, namely natural, human, physical, financial, social and instituional, ranged from 43.11 to 69.43, which indicate that the status of livelihoods in Buru is less sustainable in the natural field, while in South Buru it less sustainable in the human, physical and financial fields. Meanwhile, other fields indicate a fairly sustainable status. This study also identified there were 17 sensitive attributes from all fields that were supporting or hindering factors for the livelihood of tuna hand line fishermen in the research location. This finding has been expected to become a reference in improving the sustainability of the livelihoods of tuna hand line fishermen on Buru Island.